Functional outcome in adults treated for both bone forearm fractures with intramedullary square nails - Kulkarni, Vidisha S.; Vishwakarma, Utkarsh K.; Kulkarni, Sunil G. (International Journal of Research in Orthopaedics, 2025)
Background: The forearm fractures are considered intraarticular due to functional characteristics and spatial orientation. These fractures require anatomic reduction to maintain axial and rotational stability and preserve bone length with absolute stability for adequate healing to restore function. Open reduction and internal fixation is accepted as the treatment of choice for both bone forearm fractures according to many studies. However, it can result in complications like extensive soft tissue damage, evacuation of fracture hematoma, periosteal damage, radioulnar synostosis, neurovascular injury, compartment syndrome, delayed union, non-union, infection, refracture after implant removal. Intramedullary nailing is an alternative technique to avoid the above problems, with the advantages of minimal incision, no periosteal stripping, faster healing and biologic fixation. This study evaluates the functional outcome in adults treated for both bone forearm fractures with intramedullary square nail fixation at our institute. Methods: 113 patients with closed both bone forearm fractures were treated with Intramedullary square nail fixation between January 2014 to December 2023. There were 54 (22A) type fractures, 44 (22B) type fractures, 15 (22C) type fractures. Functional outcome was assessed based on Anderson’s criteria. Results: 105 patients had excellent to satisfactory results while fixation in 8 patients resulted in failures based on Anderson’s criteria. Conclusions: Intramedullary nailing is a simple, safe and effective method of alternative fixation of both bone forearm fractures that is associated with closed reduction, early union, biologic fixation, low infection rate, small cosmetic scars, less blood loss, shorter operating time, and less risk of compartment syndrome.